Analisis Faktor-Faktor Yang Mempengaruhi Implementasi Akuntansi Pada Usaha Kecil Menengah Di Kabupaten Cilacap - Rokhmah Agus Ciptaningsih (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2011)
The aims of research are first to analyze the simultaneously effect of educational level, firm’s age and motivation on the implementation of accounting, to analyze the partially effect of educational level on the implementation of accounting, to analyze the partially effect of firm’s age on the implementation of accounting, to analyze the partially effect of motivation on the implementation of accounting and to analyze the variable that have a dominant effect on the implementation of accounting at small and medium enterprises in Cilacap Regency, between the level of education, firm’s age and motivation. The research was conducted in working area of Dinas Perindustrian Perdagangan dan Koperasi in Cilacap Regency. The amounts of respondents used in this research of 103 entrepreneur, sampling technique used in this research is probability sampling (selected sample), whereas determination of amount of sample used the Slovin formula. To test the first, second, third and fourth hypotheses, it has used multiple linear regression analysis, then to test the fifth hypothesis, it has used elasticity coefficient of regression analysis. Based on the result of multiple linear regression analysis, it has got the value of computed-F is greater than value of F table, therefore the first hypothesis is accepted. The results of multiple linear regression analysis also showed that the value of computed-t of educational level variable on the implementation of accounting is smaller than value of t table, the value of computed-t of firm’s age variable on the implementation of accounting is greater than value of t table and the value of computed-t of motivation variable on the implementation of accounting is greater than value of t table, therefore the second hypothesis is rejected, whereas the third and fourth hypotheses is accepted. Furthermore, based on the elasticity coefficient of regression analysis, it has got the value of E3 is greater than value of E1 and E2, therefore the fifth hypothesis is accepted. Based on the result of data analysis, it can be concluded that educational level, firm’s age and motivation have significant effect on the implementation of accounting, educational level has no significant effect on the implementation of accounting, firm’s age has significant effect on the implementation of accounting, motivation has significant effect on the implementation of accounting and motivation has the dominant effect on the implementation of accounting at small and medium enterprises in Cilacap Regency. From the conclusions, the implications are first the owner at once the managers of small and medium enterprises in Cilacap Regency need to maintain the existence of a business carried on continuously through the application of professional management in addition to trying to motivate ourselves continuously by providing stimuli associated with the achievement of individual or business entity. The limitations of research include the variables that have affect on the implementation of accounting measurement limited only to the educational level, firm’s age and motivation. In addition, respondent of research is also limited to the owner at once the manager of small and medium enterprises in Cilacap Regency.